The Influence of Good Corporate Governance and Profitability on Firm Value of Banking Sub Sector Companies - Faoziyanti, Arista; Renny, Renny (PT. EQUATOR SINAR AKADEMIA, 2024)
Firm value is the investor's perception of the company's level of success in providing maximum prosperity to shareholders. This research aims to determine and analyze the influence of managerial ownership, institutional ownership, independent commissioner, audit committees, and profitability on firm value either partially or simultaneously. The object used in this research are Banking Sub Sector Companies which are listed on the Indonesia Stock Exchange for the 2019-2022. The sampling technique uses purposive sampling. The sample consisted of 11 companies from the Banking Sub Sector Companies for the 2019-2022 period. The data analysis techniques used were descriptive statistics, classical assumption tests, and panel data regression analysis using EViews software version 12. Based on the results of panel data regression analysis, it shows that partially, the good corporate governance proxied by managerial ownership, institutional ownership, independent commissioners and audit committees has no effect on firm value, while the profitability proxied by return on assets has an effect on firm value. Simultaneously, managerial ownership, institutional ownership, independent commissioner, audit committees, and profitability influence on firm value with a significance level of 0,000 and Adjusted R2 value of 97,42%.